American military aviation the indispensable arm - Gross, Charles Joseph (Centennial of flight series, 2002)
Discusses major developments in aircraft, doctrine, training, and operations. The author also provides discussions of airlife, in-flight refueling, military budgets, industry, and inter-service squabbling. He deftly sketches the evolution of the air arms of each of the different services and provides clear analyisis of military budgets.